2006
DOI: 10.1007/s00203-006-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of phytopathogenic fungus Botrytis cinerea as a potential tool for identifying pathogenicity factors, therapeutic targets and for basic research

Abstract: Botrytis cinerea is a phytopathogenic fungus causing disease in a substantial number of economically important crops. In an attempt to identify putative fungal virulence factors, the two-dimensional gel electrophoresis (2-DE) protein profile from two B. cinerea strains differing in virulence and toxin production were compared. Protein extracts from fungal mycelium obtained by tissue homogenization were analyzed. The mycelial 2-DE protein profile revealed the existence of qualitative and quantitative difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 37 publications
3
50
0
1
Order By: Relevance
“…Proteins can also be separated using 1-dimensional (based on size only) or 2-dimensional (based on charge and size) protein gel electrophoresis (Gallagher, 2006; Rabilloud and Lelong, 2011), or chromatography (e.g., ultra-high speed MALDI-TOF and high mass resolution MALDI FTICR imaging MS) (Spraggins et al, 2016). A comparative proteomic analysis of two B. cinerea strains 1.11 and 2100 identified proteins that play crucial roles in their differential virulence, including housekeeping enzymes, such as malate and glyceraldehyde dehydrogenases (Fernández-Acero et al, 2007). In another research using shotgun proteomics, 126 proteins were altered in the proteome secreted by B. cinerea , of which 13 were pectinases that are involved in cell wall degradation (Shah et al, 2009).…”
Section: Proteomicsmentioning
confidence: 99%
“…Proteins can also be separated using 1-dimensional (based on size only) or 2-dimensional (based on charge and size) protein gel electrophoresis (Gallagher, 2006; Rabilloud and Lelong, 2011), or chromatography (e.g., ultra-high speed MALDI-TOF and high mass resolution MALDI FTICR imaging MS) (Spraggins et al, 2016). A comparative proteomic analysis of two B. cinerea strains 1.11 and 2100 identified proteins that play crucial roles in their differential virulence, including housekeeping enzymes, such as malate and glyceraldehyde dehydrogenases (Fernández-Acero et al, 2007). In another research using shotgun proteomics, 126 proteins were altered in the proteome secreted by B. cinerea , of which 13 were pectinases that are involved in cell wall degradation (Shah et al, 2009).…”
Section: Proteomicsmentioning
confidence: 99%
“…Although not many proteomic data are available for filamentous fungi, despite their importance and the availability of sequenced genomes (Kim et al 2007), the utility of proteomics studies has been demonstrated by studies of the mycelia proteome (Ebstrup et al 2005;Fernandez-Acero et al 2007;Yajima and Kav 2006), secretome (Yajima and Kav 2006;Paper et al 2007) and subproteomes (Aisif et al 2006;Schmitt et al 2006), with identification and functional analysis of their proteins or differentially expressed proteins as a response to changing conditions or development stages.…”
mentioning
confidence: 99%
“…The role of these housekeeping enzymes seems to be the preparation of the infection of the host plants (Ebstrup et al, 2005). To elucidate this hypothesis, we compared 2-DE maps from B. cinerea strains differing in virulence and toxin production (Fernández-Acero et al, 2007). This study shows a clue about the role of these enzymes in pathogenicity, by differential expression levels between strains, pH variation or oxalic acid production.…”
Section: Mapping Fungal Proteomesmentioning
confidence: 96%
“…The averages of analytical and biological coefficients of variance are used for calculation (Jorge et al, 2005). Only those changes consistently present in all the extract replicates, whose quantitative differences are higher than the corresponding biological and analytical variance, should be considered (Fernández-Acero et al, 2007).…”
Section: Experimental Design Of Proteomic Studies Based On 2-dementioning
confidence: 99%